2005
DOI: 10.1021/bm049350u
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Coatings from Reactive Star Shaped PEG-stat-PPG Prepolymers and Grafted Linear PEG for Biological and Medical Applications

Abstract: Grafting of poly(ethylene glycol) (PEG) is a common strategy for reducing nonspecific interactions of surfaces with proteins. We have used grafting at "cloud point" solution conditions that ensures maximum grafting density of linear methoxy terminated PEG-aldehyde (mPEG-ald, M(w) = 5000 and 30000). In an alternative approach, surfaces were modified with layers prepared from isocyanate terminated, star shaped poly(ethylene glycol-stat-propylene glycol) prepolymers (80% ethylene glycol, six arms, M(w) = 3000, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
100
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 24 publications
4
100
0
Order By: Relevance
“…Otsuka et al 38,39 reported a contact angle of water-in-air of 47°, to be compared to 40°in this work, for a PEG 5000 coating.…”
Section: Resultsmentioning
confidence: 50%
“…Otsuka et al 38,39 reported a contact angle of water-in-air of 47°, to be compared to 40°in this work, for a PEG 5000 coating.…”
Section: Resultsmentioning
confidence: 50%
“…[33,34] The non-fouling properties of star PEG coatings were compared to surfaces modified with linear methoxy-terminated PEO chains and BSA. [33,73] In both cases, the star PEG system exhibited superior non-fouling properties. In contrast to the prevention of protein adsorption, films with thicknesses between 3 and 10 nm were not able to prevent non-specific cell adhesion under standard cell culture conditions (10% fetal calf serum).…”
Section: The Star Peg Systemmentioning
confidence: 99%
“…These amino groups have been detected by reaction with the non-fluorescent 4-chloro-7-nitrobenzofurazan (NBF) to the fluorescent derivative [34] and by gas-phase derivatization with pentafluorobenzaldehyde followed by X-ray photoelectron spectroscopy (XPS) analysis. [73] Thus, the surface will be covered by a densely crosslinked layer of PEG chains that contains a fraction of free amine groups that can be further functionalized. [74] Figure 3 shows the chemical reactions that occur during film formation and presents a model of the resulting surface coatings.…”
Section: The Star Peg Systemmentioning
confidence: 99%
“…Recently, they have been widely investigated in terms of micellar aggregation in solution because of their well-defined macromolecular architecture [27,28]. In addition, the aggregates of star polymers which have amino groups, hydroxyl groups or carboxylic acid groups in the side chains have versatile applications in medicine and biology [29][30][31], catalytical chemistry [32][33][34], and nanotechnology [35,36]. For example, Kumacheva's group recently reported fast photoactivated synthesis of stable fluorescent silver nanoclusters [37] and other semiconductor or magnetic nanoparticles [38] by employing polymer microgels with concentrated carboxyl groups as templates.…”
Section: Introductionmentioning
confidence: 99%